SAT0529 Prolonged tnf-inhibitor treatment duration is associated with lower risk of hand osteoarthritis progression in patients with recent-onset rheumatoid arthritis after 10-year follow-up. (15th June 2017) - Loef, M; Kroon, FP; Bergstra, SA; Pol, JA van der; Lems, WF; Kerstens, PJ; Allaart, CF; Kloppenburg, M
Abstract : Background: Increasing evidence indicates involvement of the pro-inflammatory cytokine TNF-α in hand osteoarthritis (OA) pathogenesis. Ten years clinical and radiologic follow-up of the BeSt study, a randomized trial primarily designed to investigate targeted treatment in rheumatoid arthritis (RA) patients, offered the unique opportunity to study the long-term effects of TNF inhibitors (TNFi) on the development and progression of hand OA. The distal interphalangeal joints (DIPs) are rarely affected in RA, which allowed to evaluate primary OA separately. Objectives: To investigate the effect of TNFi on incidental and progressive radiographic hand OA after 10-year follow-up in recent-onset RA patients. Methods: At baseline and 10-year follow-up 262 patients (mean age 52 years, 66% women) were available for radiologic assessment of hand OA. Eighteen interphalangeal joints (IPs) were scored for osteophytes (OP) using the Osteoarthritis Research Society International (OARSI) atlas (0–3; summated score 0–54), and according to the Kellgren-Lawrence (KL) scoring method (0–4; summated score 0–72). Incidental OA was defined as an increase ≥1 in summated OP score or ≥2 in summated KL score in absence of OA at baseline, and progressive OA as an increase ≥3 in summated OP or KL score in presence of OA at baseline, based on the smallest detectable change. TNFi treatment and disease activity score (DAS) were assessed on standardized visits at a three-monthly interval. Associations between duration of TNFi treatment in months and incidental and progressive OA were analyzed using generalized linear models with Poisson distribution and robust standard errors, while adjusting for age, gender, time averaged DAS, time averaged Sharp-van der Heijde score and hand OA severity at baseline. Results: Based on the OP score, 126 patients (48%) were classified with OA at baseline in the DIPs and 82 patients (31%) in the proximal IPs (PIPs). Incidental OA developed in 33% of patients in DIPs and in 42% in PIPs. Progressive OA occurred in 30% of patients in DIPs and in 38% in PIPs. Of patients with and without OA at baseline, irrespective of joint location, 63% and 55% were treated with TNFi, with a median treatment duration of 47 and 36 months, respectively. No effect of TNFi treatment duration was seen on incidental hand OA. On progressive hand OA, every month of TNFi treatment resulted in a reduced relative risk (RR) of OA progression in DIPs with a RR (95% confidence interval) of 0.987 (0.978–0.996), but not in the PIPs. The results from the analyses with the KL scoring method were comparable to the OP score, as shown in table 1 . Conclusions: Prolonged TNFi treatment is associated with a reduced relative risk on radiologic hand OA progression in DIPs, but not in PIPs, after 10 years. Although the effect sizes are small, these results provide evidence for influence of TNF-α in hand OA pathogenesis. Disclosure of Interest: M. Loef: None declared, F. Kroon: None declared, S. A. Bergstra: None declared, J. van der Pol: None declared, W. Lems: None declared, P. Kerstens: None declared, C. Allaart Grant/research support from: The BeSt study was designed by the investigators and supported by a government grant from the Dutch Insurance Companies, with additional funding from Schering-Plough B.V. and Janssen B.V., M. Kloppenburg: None declared